2019
DOI: 10.5222/tmcd.2019.154
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CMV and Rubella Seroprevalence and Age Related Distribution in Pregnant Women

Abstract: ÖZ Amaç: Bu çalışmada, gebelerde rubella ve sitomegalovirus (CMV) seroprevalansını belirlemek ve yaş grupları ile ilişkisini araştırmak amaçlandı. Yöntem: Ocak 2016 -Ocak 2019 tarihleri arasında, üçüncü basamak bir üniversite hastanesi merkez mikrobiyoloji laboratuvarında, 20. gebelik haftası ve altındaki gebelere ait hasta serumlarında, enzyme-linked fluorescent assay yöntemiyle çalışılan rubella antikorları, CMV antikorları ve CMV avidite testleri, geriye dönük olarak incelendi. Bulgular: Çalışmaya katılan g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Upon reviewing recent CMV seroprevalence studies from various cities in Turkey, it was found that CMV IgG seropositivity varied from 94% to 100% [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reviewing recent CMV seroprevalence studies from various cities in Turkey, it was found that CMV IgG seropositivity varied from 94% to 100% [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing recent CMV seroprevalence studies from various cities in Turkey, it was found that CMV IgG seropositivity varied from 94% to 100% [27,28,[30][31][32][33][34][35][36][37] (Table 4). The variability in seropositivity has been linked to factors such as living conditions, economic and demographic characteristics, hygiene, and cultural and behavioral factors [32].…”
Section: Discussionmentioning
confidence: 99%